2016
DOI: 10.1039/c5sc03006d
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic iron–iron and iron–zinc complexes of the redox-active ONO pincer ligand

Abstract: Synthetic and magnetic studies of homo- and heterobimetallic complexes of the redox-active ONO pincer ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The iron–ligand bond lengths, angles, and interatomic distances within the NNO moieties are very similar for both molecules and suggestive of the ISQ ligand oxidation state. 14,1820 The iron–ligand bond lengths in complex 2 (average bond distances: Fe–O 1.928 Å, Fe–N imino 1.884 Å, Fe–N pyridyl 1.963 Å) are slightly shorter than those in heteroleptic complex 1 (Fe–O 1.957 Å, Fe–N imino 2.014 Å, Fe–N pyridyl 2.102 Å). On the contrary, the ligand-based interatomic distances in 2 (average bond distances: C–O 1.320 Å, C–N imino 1.368 Å) are slightly longer than those in complex 1 (C–O 1.281 Å, C–N imino 1.339 Å).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iron–ligand bond lengths, angles, and interatomic distances within the NNO moieties are very similar for both molecules and suggestive of the ISQ ligand oxidation state. 14,1820 The iron–ligand bond lengths in complex 2 (average bond distances: Fe–O 1.928 Å, Fe–N imino 1.884 Å, Fe–N pyridyl 1.963 Å) are slightly shorter than those in heteroleptic complex 1 (Fe–O 1.957 Å, Fe–N imino 2.014 Å, Fe–N pyridyl 2.102 Å). On the contrary, the ligand-based interatomic distances in 2 (average bond distances: C–O 1.320 Å, C–N imino 1.368 Å) are slightly longer than those in complex 1 (C–O 1.281 Å, C–N imino 1.339 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The geometry around iron (τ of 0.52) is intermediate between trigonal bipyramidal and square pyramidal. The iron–ligand bond lengths (Fe–O 1.9572(10); Fe–N 2.0136(12) Å) as well as ligand-based interatomic distances (O1–C1 1.2809(17); N1–C6 1.3390(17) Å) are characteristic of the ISQ ligand oxidation state. , A metrical oxidation state value of −0.69 (±0.04) was determined for the NNO ISQ ligand of 1 . Density functional theory (DFT) calculations (B3LYP, def2-TZVP) show a broken-symmetry S = 2 spin state (⟨ S 2 ⟩ = 6.8) as the ground state (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray bond parameters in conjunction with the DFT calculations predicted a contribution of both L SPh ISQ · – and L SPh IQ states to the ground electronic states of 1 – 5 , which are defined as ligand‐based mixed‐valence complexes of types trans ‐[Co II (L SPh ISQ · – )(L SPh IQ )X]. The delocalized states are defined as Robin–Day Class III states of types trans ‐[Co II (L SPh ISQ 0.5 · – ) 2 X]. The investigation revealed that [ 1 – 5 ] exhibit different electronic states in solutions and solids because of tautomeric equilibria of types trans ‐[Co II (L SPh ISQ 0.5 · – ) 2 X] ⇌ trans ‐[Co III (L SPh ISQ · – ) 2 X]; [ 1 – 5 ] + and [ 1 – 5 ] – in solutions establish tautomeric equilibria of types [Co III (L SPh ISQ 0.5 · – ) 2 X] + ⇌ [Co II (L SPh IQ ) 2 X] + and [Co III (L SPh ISQ 0.5 · –1.0– ) 2 X] – ⇌ [Co II (L SPh ISQ · – ) 2 X] – .…”
Section: Introductionmentioning
confidence: 93%
“…Transition‐metal complexes L OO H 2 , L NO H 2 , and L NN H 2 exist in three different electronic states, as depicted in Scheme , within a relatively small potential range. These features of such redox non‐innocent ligands open up the opportunity to build ligand‐based mixed‐valence complexes of transition‐metal ions …”
Section: Introductionmentioning
confidence: 99%
“…Differing ligand environments, correlated with distinct electronic properties, allow each metal center to adopt a unique role in the overall reaction , . Accordingly, a number of bio‐inspired, unsymmetric complexes ― not only of iron, but with other metals ― have been reported in recent years, which merge unique coordination environments …”
Section: Introductionmentioning
confidence: 99%